2009
DOI: 10.1097/ncc.0b013e3181aaf124
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Champion's Health Belief Model Scale for Breast Cancer Screening Behaviors Among Iranian Women

Abstract: Breast cancer is a global issue that continues to be the most diagnosed cancer in women. The incidence of breast cancer is increasing, and the incidence age for Iranian women is at least 10 years earlier than in western countries. Beliefs related to breast cancer have been found to be a factor in a woman's decision about breast screening behavior, and a valid and reliable questionnaire is necessary to the development of education interventions in this area. The aim of the current study was to translate the Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…For first time Taymoori et al, have used the Farsi version of the Champion Health Belief Model Scale to measure health beliefs related to breast self-examination and mammography in Iranian women (Taymoori and Berry, 2009). According their study Iranian women had the lowest perception of susceptibility and confidence to perform BSE but the highest barriers to mammography in compression with the USA, UK, Jordan, Turkey, and Lithuania women.…”
Section: Discussionmentioning
confidence: 99%
“…For first time Taymoori et al, have used the Farsi version of the Champion Health Belief Model Scale to measure health beliefs related to breast self-examination and mammography in Iranian women (Taymoori and Berry, 2009). According their study Iranian women had the lowest perception of susceptibility and confidence to perform BSE but the highest barriers to mammography in compression with the USA, UK, Jordan, Turkey, and Lithuania women.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, the perceived severity and susceptibility scales showed reliability coefficients of 0.82 and 0.84, respectively. In the current study, the Cronbach's alpha coefficients were 0.72 and 0.73 for the perceived benefits and barriers scales, respectively (Taymoori and Berry, 2009). The studied socio-demographic items were age, marital status, employment status, educational level, family history of breast cancer, and participant's health insurance.…”
Section: Methodsmentioning
confidence: 99%
“…The instrument used in this study was the health belief model questionnaire was modified for Iranian women (Taymoori and Berry 2009).…”
Section: Methodsmentioning
confidence: 99%